Optimization of salt washing protocols for surimi production from invasive blackchin tilapia (Sarotherodon melanotheron): Molecular and functional properties - Theeraphol Senphan; Natthapong Mungmueang; Md. Sazedul Hoque; Chodsana Sriket; Soottawat Benjakul; Natchaphol Buamard; Kittima Leelapongwattana; Sitthipong Nalinanon (Food Chemistry X, 2025)
), introducing novel salt washing protocols. Ten treatments were evaluated including conventional washing, single/multiple salt washing (0.3-0.9 % NaCl), and pH-shifting methods. Molecular analyses (SDS-PAGE, ATR-FTIR and SEM) revealed myofibrillar protein preservation and distinct structural modifications. The optimized 0.6 % NaCl protocol achieved selective heme protein removal while preserving myofibrillar integrity, yielding superior gel chemistry (whiteness: 76.47 vs. 71.04) and highest sensory acceptance (7.33 vs. 6.40). pH-shifting enhanced protein recovery (68.59 %) but caused molecular aggregation and network disruption, reducing gel strength by 82 %. Molecular analysis demonstrated that salt washing selectively removes chromoproteins while preserving essential gel-forming proteins, whereas pH-shifting caused protein aggregation. SEM confirmed dense protein matrices in salt-washed samples versus fragmented networks in pH-treated surimi. This chemistry-guided approach transforms invasive species into functional protein ingredients.
Keywords: Meat and Animal Product Quality; Protein Hydrolysis and Bioactive Peptides; Aquaculture Nutrition and Growth